2019
DOI: 10.1037/pag0000382
|View full text |Cite
|
Sign up to set email alerts
|

Older adults make greater use of word predictability in Chinese reading.

Abstract: An influential account of normative aging effects on reading holds that older adults make greater use of contextual predictability to facilitate word identification. However, supporting evidence is scarce. Accordingly, we used measures of eye movements to experimentally investigate age differences in word predictability effects in Chinese reading, as this non-alphabetic language has characteristics that may promote such effects. Wordskipping rates were higher and reading times lower for more highly predictable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 87 publications
(219 reference statements)
19
33
0
1
Order By: Relevance
“…First, the results of the word-level measures analyses replicated those of previous studies, which state that older readers need more fixation time for comprehending text. However, we could not determine the effect of age on average saccade length, which is also consistent with the scope of the findings of a recent study by Zhao et al (2019). Second, with regards to the fixation time measures on target words, older readers fixated on these words for a longer time and re-fixated on them more often than younger readers, which also mirrors previous findings of studies on both Chinese and alphabetic text reading (Kliegl et al, 2004;Rayner et al, 2006;Rayner, 2009;Rayner, Castelhano & Yang, 2010;Kemper & McDowd, 2006;Kemper & Liu, 2007;Paterson, McGowan & Jordan, 2013a;Paterson, McGowan & Jordan, 2013b;Paterson, McGowan & Jordan, 2013c;McGowan et al, 2014;Zang et al, 2016;Wang et al, 2018a;Wang et al, 2018b).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…First, the results of the word-level measures analyses replicated those of previous studies, which state that older readers need more fixation time for comprehending text. However, we could not determine the effect of age on average saccade length, which is also consistent with the scope of the findings of a recent study by Zhao et al (2019). Second, with regards to the fixation time measures on target words, older readers fixated on these words for a longer time and re-fixated on them more often than younger readers, which also mirrors previous findings of studies on both Chinese and alphabetic text reading (Kliegl et al, 2004;Rayner et al, 2006;Rayner, 2009;Rayner, Castelhano & Yang, 2010;Kemper & McDowd, 2006;Kemper & Liu, 2007;Paterson, McGowan & Jordan, 2013a;Paterson, McGowan & Jordan, 2013b;Paterson, McGowan & Jordan, 2013c;McGowan et al, 2014;Zang et al, 2016;Wang et al, 2018a;Wang et al, 2018b).…”
Section: Discussionsupporting
confidence: 86%
“…However, contrary to what we had expected, we did not observe any significant differences in the average saccade length between the two age groups. As previous studies on effects of age on Chinese readers have also shown no differences in age groups in terms of saccade length, the our findings regarding sentence-level measures were consistent with previous research (Zhao et al, 2019;Li et al, 2018).…”
Section: Sentence-level Measures Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…A final consideration that also has received little attention to date concerns whether older Chinese readers make greater use of word predictability to offset the difficulties they experience. Only one study has been reported to date [161]. This showed word predictability has a larger facilitatory influence on reading times for older adults but no corresponding effect on word-skipping.…”
Section: Aging and Eye Movement Control In Chinese Readingmentioning
confidence: 87%
“…However, the effects show clearly that older readers experience considerably greater reading difficulty. Compared to young adults, they read much more slowly (often almost twice as slow) and make more and longer fixations and regressions [154,155,158,160,161]. However, by contrast with evidence from alphabetic languages, there is no indication that older Chinese readers use a more risky reading strategy to compensate for this slower reading.…”
Section: Aging and Eye Movement Control In Chinese Readingmentioning
confidence: 89%